(untitled) (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2024)
This study focuses on comics translation through a specific case: La Casa de Paco Roca, addressing themes such as memory, nostalgia, and emotional bonds that we establish with places we call «home». The main objective is to determine the approaches, methods, and techniques used by the translator and analyze the coherence between the text and the image, comparing the original work with its translation into Turkish. In this context, the intention is to exemplify limitations in comic translation and propose methods to overcome them. The process has been carried out in the following phases: a comparative reading of the original text and its Turkish translation, and the identification of features presented in the translation at different levels of analysis: translation of sociocultural references, translation of linguistic-discursive references, translation of onomatopoeias, and translation of exclamatory sentences. In conclusion, the translator generally succeeds in capturing and conveying the essence and atmosphere of the original story, using various translation techniques, such as adaptation, linguistic amplification, compensation, discursive creation, equivalence, etc. However, colloquial language differs in the translated version, probably due to a self-censorship mechanism by the publisher or the translator to avoid offending Turkish readers’ sensibilities. It is concluded that the translator finds creative solutions to preserve the work’s humor, tone, and emotion.